A new species of the sponge-associated pontoniine shrimp genus Nippontonia Bruce & Bauer, 1997 (Decapoda, Caridea, Palaemonidae) from Sabah, Malaysia - Fransen, Charles H.j.m. (Zootaxa, 2013)
A sponge-associated species of the genus Nippontonia new to science is described from Semporna, Sabah, Malaysia. The only other species in the genus is also known to be a sponge-dweller. The new species can be distinguished from its congener by a suite of characters mainly of the anterior appendages.